1880 Miss. Rev. Code 776-77, §§ 2986-88 - (:unkn) unknown (My University, 1880)
Ch. 77, §§ 2986-88: It shall not be lawful for any person to sell to any minor or person intoxicated knowing him to a a minor or in a state of intoxication, any weapons of the kind or description in the foregoing section described, or any pistol cartridge and on conviction he shall be punished by a fine not exceeding two hundred dollars, and if the fine and costs are not paid, be condemned to hard labor under the direction of the board of supervisors or of the court not exceeding six months. § 2987. Any father who shall knowingly suffer or permit any minor son under the age of sixteen years to carry concealed, in whole or in part, any person of the kind or description in the forgoing section described, shall be deemed guilty of a misdemeanor, and on conviction, shall be fined not less than twenty dollars, nor more than two hundred dollars, and if the fine and costs are not paid, shall be condemned to hard labor as provided in the proceeding section. § 2988. Any student of any university, college, or school, who shall carry concealed, in whole or in part, any weapon of the kind or description in the foregoing section described, or any teacher, instructor or professor who shall knowingly, suffer or permit any such weapon to be carried by any student or pupil, shall be deemed guilty of a misdemeanor and on conviction be fined not exceeding three hundred dollars, and if the fine and costs are not paid, be condemned to hard labor as above provided.
Keywords: CARRY - CONCEALED; TRANSFER - INCOMPETENTS; TRANSFER - MINORS